2021
DOI: 10.1186/s41983-021-00381-6
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological profile of brain tumors in Cameroon: a retrospective study

Abstract: Background Brain tumors represent group of neoplasms originating from intracranial tissues and the meninges. The aim of this study was to determine the epidemiological profile of brain tumors seen in a referral health center in Cameroon. We carried out a 10-year retrospective study in the neurosurgical, neurology, pathology, oncology and radiotherapy units of our hospital. Results We found 150 complete case files accounting for 0.7% of total admiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
(33 reference statements)
1
1
0
Order By: Relevance
“…Headaches, focal signs (motor or sensory signs), and seizures were the most common first signs or symptoms among Palestinian patients. These findings were similar to those reported in a recent study in Cameroon [ 27 ] and Saudi Arabia [ 28 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Headaches, focal signs (motor or sensory signs), and seizures were the most common first signs or symptoms among Palestinian patients. These findings were similar to those reported in a recent study in Cameroon [ 27 ] and Saudi Arabia [ 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…Meningiomas were the most common group of tumors identified in different studies around the world, including the USA (42.1%) [ 14 ], Korea (37.9%) [ 20 ], Lebanon (29.6%) [ 17 ], Northeast India [ 25 ], and Georgia [ 23 ], while in our study, the most common group of tumors identified in Palestinian adolescents and adults was diffuse astrocytic and oligodendroglial tumors (33%). In our study, the most commonly identified histopathological type was glioblastoma, while meningioma was the most common histopathological type identified in the USA [ 14 ], Korea [ 20 ], Jordan [ 6 ], Cameroon [ 27 ], and Austria [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study of the Indian population, the frequency of brain tumours is highest in the 5th decade, while our study shows the frequency to be highest in the 4th decade [8]. The most common presenting symptom was headache (53%), followed by vomiting (28%), which is comparable to the study of Western population, where headache was the most common symptom [9,11]. In our study and that of the western population, supratentorial tumours predominate over infratentorial tumours [11].…”
Section: Discussionsupporting
confidence: 74%
“…Recent advances in molecular biology have improved our understanding of glioma pathogenesis, and several clinically significant genetic alterations have been In our study, males (68%) outnumbered females (32%). In studies of the Indian population as well as the western population, the incidence of brain tumours is more common in men [8,9]. Study of brain tumours from North-East Indian population [10] showed the age of incidence was highest in 20-39 years age group which may be compared to that of our study (31-40 years followed by 21-30 years age group).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation